Reorganization of brain networks in olfactory groove meningioma patients: a pilot resting-state fMRI study - Filimonova, Elena; Pashkov, Anton; Poptsova, Aleksandra; Moysak, Galina; Martirosyan, Azniv; Prozorova, Polina; Kurilov, Vladimir; Rzaev, Jamil (Frontiers in Neurology, 2025)
BackgroundOlfactory groove meningioma (OGM) is frequently associated with neuropsychological and behavioral impairments. However, there is currently a lack of evidence on the pathobiology of these functional alterations. In this study, our objective was to evaluate functional connectivity disturbances in patients with OGMs compared to healthy controls.MethodsNineteen patients with OGMs and twenty healthy controls were enrolled. The seed-based functional connectivity analysis used the main hubs of the default mode network (DMN), salience network (SN), and fronto-parietal network (FPN) as seeds. Region-of-interest (ROI)-to-voxel second-level analysis was conducted, revealing the most significant clusters of differences in brain functional connectivity between the groups.ResultsPatients with OGMs demonstrated significant alterations in resting-state functional connectivity within the DMN, SN, and FPN compared to controls. Specifically, within the DMN, we identified abnormal connectivity patterns involving the medial prefrontal cortex bilaterally, posterior cingulate cortex bilaterally, and right posterolateral cortex. In the SN, we observed enhanced functional connectivity between the anterior cingulate cortex bilaterally and left frontal, temporal, and insular regions. Additionally, the FPN exhibited disrupted connectivity of the right posterior parietal cortex with other brain areas. Notably, some connectivity changes were related to perilesional edema volume, visual acuity, and clinical metrics (KPS and MoCA scores).ConclusionWe revealed significant alterations in DMN, SN, and FPN function in patients with olfactory groove meningiomas compared with controls. These changes were associated with clinical variables and lesion characteristics. To our knowledge, this is the first report on rs-fMRI alterations in patients with olfactory groove meningiomas.